Viscoelasticity of blood and viscoelastic blood analogues for use in polydymethylsiloxane in vitro models of the circulatory system - Laura Campo-Deaño (2013)
The non-Newtonian properties of blood are of great importance since they are closely related with incident cardiovascular diseases. A good understanding of the hemodynamics through the main vessels of the human circulatory system is thus fundamental in the detection and especially in the treatment of these diseases. Very often such studies take place in vitro for convenience and better flow control and these generally require blood analogue solutions that not only adequately mimic the viscoelastic properties of blood but also minimize undesirable optical distortions arising from vessel curvature that could interfere in flow visualizations or particle image velocimetry measurements. In this work, we present the viscoelastic moduli of whole human blood obtained by means of passive microrheology experiments. These results and existing shear and extensional rheological data for whole human blood in the literature enabled us to develop solutions with rheological behavior analogous to real whole blood and with a refractive index suited for PDMS (polydymethylsiloxane) micro-and milli-channels. In addition, these blood analogues can be modified in order to obtain a larger range of refractive indices from 1.38 to 1.43 to match the refractive index of several materials other than PDMS. (C) 2013 AIP Publishing LLC.